KARAKTERISTIK TEMPAT TUMBUH ANGGREK Dendrobiumspp DI DESA MATAUE KECAMATAN KULAWI KABUPATEN SIGI - Velix, Frits; Toknok, Bau; Rukmi, Rukmi (Jurnal Warta Rimba, 2020)
Dendrobium spp orchid is an orchid that grows and develops epiphytes attached to the host plant or the place of its growth. The orchid requires a place to grow with various types of specific host plants and different characteristics that exist in nature. The purpose of this research is to find out the characteristics of Dendrobium spp orchids and how to preserve Dendrobium spp orchids in nature. This research method consists of several stages, namely starting from a survey and exploration of forests in the village of Mataue BTNLL area to determine the location of orchid observation. Observe the characteristics of Dendrobium spp. Orchids in the plot. The observed data are Dendrobium spp orchids, host tree species and the surface of the bark of the Dendrobium orchid. As well as the height of the place based on elevation. The data is taken by conducting surveys and placement of deliberate observation plots (purposive sampling) with a size of 20 m x 20 m. Observation results at the study site found 5 types of trees on which Dendrobium spp orchids grow, namely: Dango (Harpullia sp), Forest Durian (Durio zibethinus Merr), Banyan (ficus sp), Neunauclea purpurea (Roxb.) Merr., Jabon / Kakabo (Anthocephalus) sp). The types of trees found as trees generally have the same characteristics, namely rough, hollow and overgrown with moss.Keywords: Karakteristik, Tempat Tumbuh Anggrek, Desa Mataue